Community involvement in post disaster re‐construction ‐ case study of the British red cross Maldives recovery program - M. Lawther, Peter (International Journal of Strategic Property Management, 2009)
Community involvement in post disaster re‐construction is an important ingredient to the overall success of housing and infrastructure redevelopment. Implementing Agencies and governments need to design post disaster re‐construction programs which promote the involvement of beneficiaries and communities in post disaster re‐construction programs, to the extent allowed by the scale and context of any given situation. By extension, the management and organisational capacities which enable community involvement in a post disaster re‐construction project need to be identified and developed to facilitate this process. The British Red Cross Maldives post – tsunami recovery program is presented as a case study to identify successes, limitations, and lessons learnt from one such project. The case study is examined to identify capacity building opportunities for community involvement in future post disaster re‐construction projects. These opportunities are presented in terms of the project procurement model chosen for implementation, active and passive methods of community involvement, and the personal skills and management structure required to facilitate community involvement in post disaster re‐construction projects.First Publish Online: 18 Oct 2010